The Tongue-in-Groove Technique in Primary and Revision Rhinoplasty - Datema, Frank R.; Lohuis, Peter J.F.M. (Facial Plastic Surgery, 2016)
The tongue-in-groove (TIG) is a conservative but powerful surgical suture technique to control tip rotation and projection, to set an appropriate alar–columellar relationship, to straighten a caudal septal deviation, and to stabilize the nasal base. TIG is suitable in primary and most revision cases and is easily combined with other surgical techniques. Seventeen years after its popularization, the TIG technique is embedded in modern-day rhinoplasty literature and teaching material. This article describes indications and considerations during external primary and revision rhinoplasty, based on clinical experience and the available literature.
Keywords: tongue-in-groove; rhinoplasty; nasal tip